Using wage rate analysis to determine software project scale - Shahzad, B. (Maxwell Science Publications, 2014)
Software development projects are usually categorized as large, medium or small scale but these terms have not been described in a quantifiable manner. Although there are some specific measures, e.g., function points, however, scholars agree that they cannot be generalized for all software projects. Project managers realize that the resource allocation for small, medium and large scale projects is intrinsically different in nature and at the same time managers struggle to identify the scale of the project. Therefore it is pertinent to be able to identify the scale of the project before resource allocation. This study presents a study which is based on quantifiable measurements of project success factors and shows a way to identify the project scales. Data from the study is used to determine and quantify project scales in terms of cost, time and team size. Wage rate analysis is used to demonstrate the validity of our results. After quantifying the project scales the underlying wage rate is compared with wage rate reported in contemporary studies to successfully validate the results of our study. Â© Maxwell Scientific Organization, 2014.